Working Conditions of Loco-Pilots (Railway Drivers) in India: A Review Study - Ranjan, Rajesh; Prasad, T. (Engineering Research: Perspectives on Recent Advances Vol. 1, 2024)
The work of the railway driver is demanding and full of responsibility. The railway driver is in charge of both safety and punctuality, a job which requires a high level of concentration and alertness. Henceforth, the work of Indian railway drivers is considered extremely stressful. They work in an environment over which they have no control, leading to an atmosphere that wrecks their schedules, disrupts their home life, and makes social activities and regular breaks very hard to plan. This paper deals with the working conditions of Indian railways drivers and the factors that lead to fatigue and stress, causing a high probability of accidents. This review of literature deals with the working conditions of Indian railway drivers which has very high importance on their total well-being and hence their productivity and entire growth and safety of the Indian railway. In summary, after reviewing of literature, it has been identified that the Indian railway drivers had difficulties in balancing work, life, and social activities.